AZADIRACHTIN : ITS EFFECTS ON EGGS AND POSTEMBRYONIC DEVELOPMENT IN SPODOPTERA MAURITIA BOISD. (LEPIDOPTERA : NOCTUIDAE) - JAGANNADH, V.; NAIR, V. S. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Eggs of Spodoptera mauritia of known ages (day 0, day 1 and day 2) were topically treated with 5µg, 10 µg or 20 µg azadirachtin and the effects of these treatments on hatchability and postembryonic development were studied. Treatments had no effect on egg hatchability, but the larvae showed high rate of mortality during postembryonic development. The significance of these findings is discussed.